Oral Proficiency in Higher Education: A Comprehensive Examination of Task-Based Language Teaching (TBLT) for ESP Students - Yulini Rinantanti; Maximus L. Nemo; Andi Asrifan; Sunarlia Limbong (AL-ISHLAH: Jurnal Pendidikan, 2024)
There have been various conceptualizations about the implementation of task-based language teaching (TBLT) in the context of English language teaching. TBLT has been proposed as a potentially efficacious approach for instructing English as a second language (ESL) in Asian settings, such as Indonesia. The present study aimed to investigate the optimal implementation of TBLT for higher education students in ESP classrooms. A cohort comprising seventy ESP students pursuing a degree in the Accounting Study Program participated as research subjects. This research used a descriptive quantitative research method. The results show that the implementation of TBLT into the teaching of speaking skills resulted in beneficial result concerning students in ESP classrooms. The findings of this study indicate a statistically significant increase in the mean scores of oral English proficiencies among students enrolled in English for Specific Purposes (ESP) courses, as seen by the comparison between pretest and post-test scores. This study can be implemented by providing opportunities for students to engage in spoken language practice rather than learning sessions primarily focused on the explicit instruction of grammatical rules and ESP students’ comprehensibility. This study can be applied in TBLT approach in the ESP classroom setting for comprehensibility in EFL students' oral English.